Identificación del plomo, benceno y tolueno en trabajadores que manipulan lubricantes y brindan servicios automotrices - L., Edgar (2002)
It was realized the quantification of blood lead, benzene (phenol) and toluene (hipuric acid) metabolites in urine of 158 mechanic and lubricant center workers. Workers usually use fuel(gasoline, kerosene and diesel-2) and other solvents (thinner, aguarras, paints diluent, etc.) which have toxic components as lead, benzene and toluene. The blood lead quantification was perfoled with the Atornlc Absorption Spectrophotometry (AAS) method it showed that blood The data was analyzed using the statistical package SPSS versión 9,0. Conclusions: The older adult has more probability of being more susceptible to secondary effects or adverse reactions for the enalapril administration or of nifedipino.